Wastewater Treatment Using a Pond System in the Rubber Processing Industry at PT. XYZ - Oktaria, Delvina; Hardoyo, Hardoyo; Natalina, Natalina (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2026)
Internationally and nationally, natural rubber (Hevea sp.) is one of the important agricultural commodities. PT. XYZ is a natural rubber processing industry that produces SIR 20 (Standard Indonesia Rubber) with a processing capacity of up to 40 tons of KK per day. In its production activities, this company produces liquid waste as a byproduct that has the potential to damage the environment. This study aims to examine the liquid waste processing process at PT. XYZ and assess the content of the waste, so that it can be disposed of safely without having a negative impact on the environment, in accordance with applicable regulations. This study uses a qualitative descriptive method to describe the liquid waste processing system and process and a quantitative descriptive method to compare the results of wastewater quality tests with quality standards. The results of observations of rubber liquid waste processing in this company use a pond system consisting of 10 ponds, namely 2 rubber trap ponds, 3 anaerobic ponds, 2 facultative ponds, and 3 aerobic ponds. Liquid waste produced from the rubber production process is flowed from one pond to another by utilizing gravity. Wastewater quality testing conducted by internal and external parties indicates that the pH, BOD, COD, TSS, Ammonia, and Total Nitrogen parameters meet the quality standards as stipulated in Appendix IV of Ministerial Regulation No. 5 of 2014 concerning Wastewater Quality Standards for Rubber Industry Activities. Therefore, the wastewater is declared safe for discharge into the environment.